HUBUNGAN STATUS SOSIAL DENGAN TINGKAT DEPRESI PADA LANJUT USIA DI RW 03 KELURAHAN AEK NAULI KOTA PEMATANGSIANTAR - Lely Melan Gultom; Lenny Lusia Simatupang (Jurnal Riset Multidisiplin Edukasi, 2025)
Background: Social problems arise due to changes in the social values of society which have an impact on the elderly who receive less attention so that they are neglected in society.Economic problems arise in the elderly when entering retirement or quitting their main job due to decreased work efficiency, resulting in a lack of income related to meeting daily needs.Lower levels of depression in individuals with higher socioeconomic status, better self-reported health, greater social capital, and greater functional independence, doing physical activity is also thought to prevent depression.Objective: This study aims to determine the relationship between social status and the level of depression in the elderly in RW 03 Ling.II Kelurahan Aek Nauli Kota Pematangsiantar.Methods: This study uses a quantitative method using a correlational design. Sampling using total sampling with a sample size of 60 respondents, the research instrument used is a questionnaire sheet.The data analysis used was spearman correlation.Results: The results showed that there was a relationship between social status and depression level with a p-value = 0.038 (a <0.05).Conslution: there is a relationship between social status and the level of depression in RW 03 Ling.II Kelurahan Aek Nauli Kota Pematangsiantar. It is recommended that future researchers can further develop the results of this research by adding variables such as quality of life.